State-of-the-Art Advances of Nanomedicine for Diagnosis and Treatment of Bladder Cancer - Chenfan Kong; Shaohua Zhang; Qifang Lei; Song Wu (Biosensors, 2022)
Bladder cancer is a common malignant tumor of the urinary system. Cystoscopy, urine cytology, and CT are the routine diagnostic methods. However, there are some problems such as low sensitivity and difficulty in staging, which must be urgently supplemented by novel diagnostic methods. Surgery, intravesical instillation, systemic chemotherapy, and radiotherapy are the main clinical treatments for bladder cancer. It is difficult for conventional treatment to deal with tumor recurrence, progression and drug resistance. In addition, the treatment agents usually have the defects of poor specific distribution ability to target tumor tissues and side effects. The rapid development of nanomedicine has brought hope for the treatment of bladder cancer in reducing side effects, enhancing tumor inhibition effects, and anti-drug resistance. Overall, we review the new progression of nano-platforms in the diagnosis and treatment of bladder cancer.